Alexander Chak’s Correspondence – historical and artistic value of the Latvian cultural heritage - Medne, Antra (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
Evaluating and grouping the literature historical relics, including the correspondences by letters between famous people, for a ground (base) we could take categories which demonstrate the qualities which have elements from the material world in an anent with a human. The cultural historian Fridrich Waidacher by researching the interconnection and selective values between material and spiritual world classified the evidences of material world in several chapters which are not strictly caged in permanent schemes (patterns). The division was made by taking F. Waidacher conception as a base and researching the correspondence by letters of Latvian poets and cultural workers: The potential value of the memory, the meaning which we ascribe to a concrete object (epistle). The historical value (a reference to a concrete period of time). The value of variability (a reference to the changes in the world). Rarity (singularity). The valueofarts. The correspondence in the Latvian literature – history is not a rarity. There are published several letters, for an example, between Mirdza Kempe and Eric Adamson; collected and are waiting for publishing – Raina and Aspazijas letters in the time from 1894 to 1929. This correspondence is made from 2499 letters in Latvian, Russian and German: 1154 letters are from Aspazija to Rainis and 1345 – from Rainis to Aspazija. The correspondence by letters for Alexandrs Chaks is more modest. There are just some letters, which were written by the poet. In collections in the Museum of Alexandr Chak and in the Museum of Literature and Music are approximately 40 letters written by other persons, which written to Alexandr Chak. For reasons of clearliness, they can be devided in: Letters of friends and greeting cards, which were sent to the poet in annual increment and also on birthdays. The letters from colleagues in which are analyzed the creative literature works. Official letters and reports which were sent from the State authorities and public organizations. Invitations and encouragements to start a literary work. This part refers to the period of time after the war when poets were „propelled“ to write more and appropriate to the leading instructions. Requests of help and money loans were always an issue, because A. Chak was not closefisted and gave the money to many suppliants. Letters from admirers. The most pleasant part of the correspondence. The correspondence by letters in nowadays is a rarity. It is a unique evidence of the beginning of 20th century which supplemented and enriched the history of Latvian literature and culture, by marking a very personal lines in lives of writers and poets. In this research are included just the main thoughts and waypoints in the diversity in A. Chak’s correspondence. The left written message by the poet – correspondence is deliberate and easy to access for researcher. The aim of the research: the evaluating the cultural heritage of the correspondence of Alexander Chak. The method of the research: the used method includes life stories, historical content and researching of the letters and personal documents from people who are involved in this research. In the history of literature are used not only such nomenclatures like biographical method, but also the method of oral history. The exploratory material – correspondence – is acquired during the biographical research and interviews. The biographical access, in general, is typical accent on a life of a person and also on the most significant stages and expression of it. Also, if the goal of a research is to analyze various life aspects or life stages of a person, these are looked up in a biographical context. The main question in those biographical researches is about interrelations between individual and the World. Material: the exploratory material is the correspondence of Alexander Chak which is collected and summed up from various museum holdings of Latvia, publications in books and private collections. Outcome: Are collected all written letters by Alexander Chak which are extant. Are collected and grouped all letters which Alexander Chak has received from other addressees. These letters are grouped and analyzed, by considering the topical principle. Conclusions: The culture of letter writing disappears. In the 20th century people wrote letters to each other which are extant and usable for the basis of source information in the exploratory work. Nowadays it is an exclusive thing, letters to be written in paper form, which helps to form and strengthen people relationship. The lifespan of an electronically letters are just so long, till they are moved to the recycle bin and completely deleted from the computer. The researchers of the next century will face the lack of documental material. The researchers of literature history in next hundred years will face the lack of documental material which will partly disturb to trace the development of a poets or a story writers character.